SOCIO-ECONOMIC FACTORS INFLUENCING POSTHARVEST LOSSES OF CASSAVA IN SAKI WEST LOCAL GOVERNMENT AREA OF OYO STATE, NIGERIA - Mazadu, Z. M.; Rasak, F. O.; Musa, U. R. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the socio-economic factors influencing post-harvest losses of cassava in Saki West Local Government Area of Oyo State, Nigeria. A multi-stage sampling technique was employed to select 120 cassava farmers, and primary data were collected using structured questionnaires. The data were analyzed using descriptive statistics and multiple regression analysis. Results revealed that the majority (75%) of respondents were male with an average age of 42 years, small farm sizes (less than 5ha), and limited access to extension services (87.67%). The results of the regression analysis indicated that marital status(p≤0.001), household size(p≤0.010), significantly influenced post-harvest losses of cassava. The major constraints faced by cassava processors included inadequate capital (90%), deterioration of tubers (70%), and low demand (74%), The study concludes that both socio-economic and biological factors play critical roles in post-harvest losses. It recommends improved access to credit, provision of modern storage and processing facilities, farmer education on post-harvest handling practices, and enhanced market linkages to reduce losses and improve the cassava value chain